ANALISIS PENGARUH INDEKS PEMBANGUNAN MANUSIA DAN PENGANGGURAN TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI BANTEN PERIODE TAHUN 2017-2021 - Tasya Siti Nurasiah (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2022)
The success of a country's development can be seen from several indicators. One important indicator in the success of the country's development is economic growth. Economic growth is state income that has experienced an aggregate national increase or an increase in output in a certain period. Each country will try to increase and provide the best to support the country's economic growth optimally. Including Indonesia, which is a developing country that seeks to increase its economic growth for the welfare of society and a better life. Conditions in developing countries such as Indonesia, the economic growth that has been achieved is also accompanied by an increase in the number of Indonesian population, a large number of Indonesian people are still unemployed. Unemployment is a problem for countries with high population growth rates, such as Indonesia. Unemployment can also affect the level of the Indonesian economy. Likewise, a high level of human development greatly determines the ability of the population to absorb and manage sources of economic growth, both related to technology and to institutions as an important means of achieving economic growth (Brata, 2004).